Propagación vegetativa de quinilla (Manilkara Bidentata, A.DC.) mediante el enraizamiento de estaquillas utilizando cámara de subirrigación en el distrito de Morales provincia de San Martín - Cervantes Owaki, Danny Daniel (2011)
Species used in the construction of bridges, poles, hardwood floors in ferrovianas lines. It is now in danger of extinction due to genetic erosion and particularly by shifting cultivation that would limit the availability of seeds in quantity and quality needed for production and replacement through reforestation programs. This study evaluated the effects of three substrate types and four doses of acid-3-indole butyric (IBA) on rooting ability of keels quinilla (Manilkara bidentata), using cameras subirrigation. The trial was conducted in the forest nursery of the Institute of Peruvian Amazon Research in San Martín (IIAP), using a completely randomized design with split plot consisting of twelve treatments, four replications and six cuttings per experimental unit. At the end of 30 days was obtained 83% rooting medium sand as a substrate using 0.8% AIB. It is necessary, the use of shadow on the propagators to reduce radiation, air temperatures and substrate within the propagators, as well as to maintain high relative humidity.